PERBANDINGAN PAPAN GIPSUM SERAT DAUN NENAS (ANANAS COMOSUS L. MERR) TERHADAP PAPAN GIPSUM KOMERSIL DILIHAT DARI SIFAT FISIS DAN MEKANIS BERDASARKAN SNI SPESIFIKASI PANEL ATAU PAPAN GIPSUM 03-6384-2000 - Fathurrahman, Hamdan; Neolaka, Amos; Arthur, Riyan (Jurnal Pendidikan Teknik dan Vokasional, 2020)
The use of synthetic fiber gipsum board began to be reduced and replaced with fiber derived from nature, one of the fibers that can be replaced is a pineapple fiber. Therefore, further research on the utilization of pineapple fiber waste as a substitute for synthetic fiber is required. This research is a comparative quantitative research using experimental method by conducting 2 (two) characteristic tests consisting of physical properties test and mechanical properties test with pineapple fiber usage of 5% and 6% as gipsum board fiber. Based on physical and mechanical properties test, it was found that pineapple fiber gipsum board with 6% fiber usage had better value and quality compared to commercial gipsum board. This result can be used as reference of testing about building materials that are environmentally friendly and can be applied as one of the material resources in vocational education. Keywords: pineapple fiber, mechanical properties, physical properties.